PENGARUH STRES KERJA DAN PUNISHMENT TERHADAP KINERJA KARYAWAN DEPARTEMEN MERCHANDISING INDOMARET CABANG BANJARMASIN - Mailiana Mailiana; Diana Hayati; Nadi Hernadi Moorcy; Ahmad Maulana (Program Studi Manajemen Fakultas Ekonomi Universitas Balikpapan, 2023)
The purpose of this study was to find out how work stress partially influences the performance of employees of the Banjarmasin Branch of Indomaret Merchandising Department, to find out how partial punishment affects the performance of employees of the Indomaret Merchandising Department Banjarmasin Branch, and to find out how work stress and punishment simultaneously influence performance of employees of the Merchandising Department of Indomaret Banjarmasin Branch The method used is a quantitative descriptive method. Data collection is in the form of distributing questionnaires. Data processing in this study used the SPSS program and the analysis tests carried out were the Research Instrument Test, the Classical Assumption Test, and the Hypothesis Test. The conclusions of this study indicate that work stress and punishment simultaneously have a significant effect on the performance of employees of the Banjarmasin Branch of Indomaret Merchandising Department. Partially, Job Stress has a negative and significant effect on Employee Performance at the Indomaret Merchandising Department, Banjarmasin Branch, meaning that the higher the Job Stress, the Employee Performance will decrease significantly, and vice versa. And partially, punishment has a positive and significant effect on employee performance, meaning that the fairer the punishment system applied to the Indomaret Merchandising Department, Banjarmasin Branch, the employee performance will increase. Suggestions from this study are that superiors from the branch level to the central level in the Indomaret Merchandising Department are expected not to overload employees with excessive tasks, this can increase high stress pressure. And to impose punishment on employees so that it can be carried out with a good warning and delivery, for example conveying it personally to the employee concerned, so that the employee does not feel pressured and there is no suggestion of excessive worry in doing work that can result in punishment.